Research impact of national higher education systems - De-Moya-Anegón, Félix (Anuario ThinkEPI, 2011)
Research impacts of national higher education systems are compared using their normalized impacts (ratio of institution´s average impact to the world´s average). Fifty countries are analyzed, taking into account their research ratio between firms and universities, as well as the homogeneity of their universities. The baseline data were obtained from SCImago Institutions Rankings system.
Keywords: Impact standardized educational systems; Higher Education; National Systems.